Microencapsulação da microalga spirulina sp. para a adição em massa fresca tipo talharim - Zen, Cindiele Karen (2018)
Cereal products, such as fresh pasta, are appropriate food options for the incorporation of functional ingredients, because of their convenience, palatability and because they are consumed by people of different age groups and at different places. In recent years, various ingredients have been used in the production of fresh pasta to improve and / or confer functional properties. Microalgae are becoming a promising alternative for food application because they are able to improve nutritional content and add functional value to food. Spirulina sp. it stands out among microalgae, because it is safe for consumption, it presents balanced chemical composition, with high protein content, vitamins, antioxidants due to the presence of phycocyanin and phenolic compounds. On the other hand, it has as its characteristic unpleasant taste and odor and when subjected to high temperatures, may have its antioxidant capacity affected. One way of ensuring the acceptability of the product by the consumer and ensuring the properties of Spirulina is by microencapsulating its biomass with a water insoluble capsule before adding it to the fresh mass in a way that does not modify the desired sensory characteristics of this product. The objective of the dissertation was to contribute to the development of functional foods added to the microalga Spirulina platensis. The work was divided in 2 studies, being the elaboration and characterization of the microparticles over time (0, 7, 14 and 30 days) and sensory analysis of the fresh mass added of the microparticles at the initial time. The formation of a microparticle with sodium alginate and calcium chloride was able to entrap more Spirulina in relation to the total solids, ratio 1: 1. This microsphere showed low solubility in water and, in addition, protected the antioxidants of Spirulina sp. when subjected to the heat treatment. Regarding the shelf-life study, the addition of microencapsulated Spirulina in the mass affected the parameters of cooking, texture and color when compared to the control mass. The sensorial analysis showed that there was no difference in the acceptability of the formulations in relation to the flavor. The attribute most cited by the judges in the application of the CATA (Check All That Apply) methodology was the firm texture. Mass with microencapsulated Spirulina proved to be a nutritious and functional food alternative. The study also showed that people are beginning to accept the incorporation of different ingredients for food processing.